Bacterial Communities in the Fruiting Bodies and Background Soils of the White Truffle Tuber magnatum - Sillo, Fabiano; Vergine, Marzia; Luvisi, Andrea; Calvo, Alice; Petruzzelli, Gianniantonio; Balestrini, Raffaella; Mancuso, Stefano; De Bellis, Luigi; Vita, Federico (Frontiers in Microbiology, 2022)
Tuber magnatum Pico is a greatly appreciated truffle species mainly distributed in Italy. Its price and characteristics are mostly depending on its geographical origin. Truffles represent a fundamental step of the life cycle of Tuber species promoting spore dissemination and consists of two main parts, gleba, the inner part, and peridium, which is in direct contact with ground soil. Within truffle, and around in the growing soils, both occurrence and abundance of different microbial species, seem to play an essential role in truffle production. The development of the next-generation sequencing (NGS) based technology has greatly improved to deepen the role of the composition of microbial communities, thus improving the knowledge on the existing relationships between microbial taxa in a specific condition. Here, we applied a metabarcoding approach to assess differences in T. magnatum samples collected from three areas from Tuscany (Italy). Peridium and gleba were analyzed separately, with the aim to distinguish them basing on their microbial composition. Also, soil samples were collected and analyzed to compare productive and unproductive truffle grounds to confirm the presence of specific patterns linked to truffle production. Results indicate that differences occurred between truffle compartments (gleba and peridium) as well as between analyzed soils (productive and unproductive), with distinctive taxa associated. Furthermore, findings also demonstrated specific characteristics associated with truffle collection areas, thus indicating a degree of microbial selection related to different environments.